The Use of Deep Learning-Based Interactive Visual Media in Improving Students' Understanding of Concepts in Various Subjects: Literature Review - Syerli Feronica; Lovita Lovita; Pahrozi Ahmad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The rapid advancement of educational technology has introduced sophisticated tools to improve classroom instruction, but students often struggle to understand abstract concepts through traditional methods. This literature review aims to analyze the role and effectiveness of deep learning-based interactive visual media in improving students' understanding of concepts in various subjects. This study uses a systematic literature review method by synthesizing academic journals, research reports, and pedagogical publications in the past decade to test the synergy between artificial intelligence-based interactive media and student learning outcomes. The analysis shows that deep learning-based interactive visual media effectively enhances cognitive engagement, facilitates the simplification of complex concepts, and improves memory retention by providing a personalized and adaptive learning experience. It is concluded that the integration of interactive visual media powered by deep learning is a significant pedagogical advance, offering educators a dynamic tool to foster deeper understanding of concepts and active student participation.